2017
DOI: 10.1186/s13104-017-2868-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study for determining the prevalence of Q fever in small ruminants and humans at El Minya Governorate, Egypt

Abstract: ObjectiveQ fever is a febrile illness caused by the bacterial pathogen Coxiella burnetii (C. burnetii) and is transmitted to humans from small ruminants via contaminated secreta and excreta of infected animals. This pathogen threatens public health; however, little is known regarding Q fever prevalence in humans and small ruminants. Therefore, we employed a cross-sectional design to determine the Q fever seroprevalence and the associated risk factors in small ruminants and their owners in El Minya Governorate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
(23 reference statements)
3
14
0
Order By: Relevance
“…[20,21,22,31,32,33,34,35,36,37,38,39,40,41,42]; nine reporting on Leptospira spp. [22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21,22,31,32,33,34,35,36,37,38,39,40,41,42]; nine reporting on Leptospira spp. [22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles probed the presence of Q fever in human and animal hosts [41,48,50,51,52]. Abdel-Moein and Hamza examined vaginal discharges and placental cotyledons from animals that had aborted and found an overall prevalence of 0.9%, with the highest prevalence of Q fever being found in goats (3.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study indicated that ticks collected on camels (Hyalomma dromedarii) and bulls (Hyalomma excavatum) imported in Egypt from Sudan were infected with C. burnetii (233). Other studies found the presence of C. burnetii in livestock with a seroprevalence of 22.5 to 32.7% in sheep, 16.8 to 28.2% in goat, and 13 to 13.2% in cattle, respectively (171)(172)(173)234). A large survey that included livestock from Western desert, Nile River Valley, and Delta region reported anti-C. burnetii Ig in 19.3% (162/840) of cattle, 8.9% (64/716) of sheep, and 6.8% (21/311) of goats (235).…”
Section: The Main Known Reservoirs Of Coxiella Burnetii: Cattle Sheementioning
confidence: 95%
“…Another study found a seroprevalence of 16.3% (15/92) in humans who lived in agricultural districts (172). A more recent (2016-2017) study in El Minya Governorate reported a seroprevalence of anti-C. burnetii IgG of 25.7% (9/35) in farmers (173). Besides a case of Q fever in a Belgian patient who developed the disease after a journey in Syria was reported (174), there is no information available regarding human seroprevalence of anti-C. burnetii Ig in the Palestinian, Lebanese, Jordanian, and Syrian populations.…”
Section: Human Q Fever Epidemiology Around the Mediterraneanmentioning
confidence: 99%